The qualitative and quantitative description of growth and condition of silver kob, A. inodorus - Schoonbee, Willem Lodewyk (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MscAgric (Animal Sciences))--University of Stellenbosch, 2006.